El papel de las mujeres amatlecas en la conservación biocultural dinámica del maíz nativo en Amatlán de Quetzalcóatl, Tepoztlán, Mor - Erica Hagman Aguilar; Montserrat Gispert Cruells (Revue d'ethnoécologie)
The mexican maize (Zea mays L.) preserved in Amatlán de Quetzalcóatl (Tepoztlán, Morelos) is an example of a dynamic biocultural conservation. The inhabitants of this community are nahuas, an ethnic group that is in resistance facing the loss of their traditions, culture and lineage. The community is located in a region of high biodiversity. In this study we pursue to identify the cultural, environmental and socio-economic factors that have contributed to the preservation of native maize in this community. Women of Amatlán had an equal participation in crop management and also played several special roles as the harvest reception at home, cooking and carrying food to the agricultural field; moreover they’re the sustenance administrator of their homes and creators of culinary transformation processes of milpa’s crop species.